Analisis Komprehensif Pasal 2 KUHP Nasional: Konsep Hukum yang Hidup dalam Masyarakat, Tantangan Implementasi, dan Implikasi terhadap Asas Legalitas Pidana Indonesia - Sangkala, Robert; Komala, Ida; Wibowo, Satria Ari; Roif, Roif; Asari, Ali; Candra, Firman Adi (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
The enactment of the National Criminal Code (KUHP Nasional) through Law No. 1 of 2023, effective from January 2, 2026, marks a paradigm shift in Indonesian criminal law by introducing Article 2, which recognizes